2013
DOI: 10.1038/nrn3589
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: The brain reward circuitry in mood disorders

Abstract: Functional MRI (fMRI)-based lie detection has been marketed as a tool for enhancing personnel selection, strengthening national security and protecting personal reputations, and at least three US courts have been asked to admit the results of lie detection scans as evidence during trials. How well does fMRI-based lie detection perform, and how should the courts, and society more generally, respond? Here, we address various questions -some of which are based on a meta-analysis of published studies -concerning t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Abnormalities in neural reward circuitry may be a key feature underlying depressive disorders, particularly the core symptom of anhedonia (Naranjo, Tremblay, & Busto, 2001; Russo & Nestler, 2013). Functional MRI (fMRI) studies have shown that, compared with healthy controls, adults with depression exhibit reduced activation to rewards in striatal regions of the brain and are less likely to adjust their behavior in response to rewards (Eshel & Roiser, 2010; Henriques & Davidson, 2000; Pizzagalli et al, 2009; Pizzagalli, Jahn, & O’Shea, 2005; Smoski et al, 2009; Steele, Kumar, & Ebmeier, 2007).…”
mentioning
confidence: 99%
“…Abnormalities in neural reward circuitry may be a key feature underlying depressive disorders, particularly the core symptom of anhedonia (Naranjo, Tremblay, & Busto, 2001; Russo & Nestler, 2013). Functional MRI (fMRI) studies have shown that, compared with healthy controls, adults with depression exhibit reduced activation to rewards in striatal regions of the brain and are less likely to adjust their behavior in response to rewards (Eshel & Roiser, 2010; Henriques & Davidson, 2000; Pizzagalli et al, 2009; Pizzagalli, Jahn, & O’Shea, 2005; Smoski et al, 2009; Steele, Kumar, & Ebmeier, 2007).…”
mentioning
confidence: 99%
“…Disruptions in reward pathways of the brain have been associated with mood and anxiety disorders (Ulrich-Lai et al, 2010;Russo and Nestler, 2013). Atypical responses to pleasurable stimuli such as food or positive social interaction might be an indication of dysfunctional reward signaling which could be a sign of mood or anxiety disorders, as summarized in this section.…”
Section: Responses To Appetitive Stimulimentioning
confidence: 97%